2017
DOI: 10.12980/jclm.5.2017j7-145
|View full text |Cite
|
Sign up to set email alerts
|

Stress-preventing effects of the anaesthetic agents 2-phenoxyethanol, MS-222, clove oil and metomidate in the Senegalese sole Solea senegalensis

Abstract: The journal implements double-blind peer review practiced by specially invited international editorial board members. Objective: To determine the effectiveness of the anaesthetic agents 2-phenoxyethanol, MS-222, clove oil and metomidate in attenuating acute handling stress in juvenile specimens of Solea senegalensis subjected to two routine stressful events specific to aquaculture and/or fish research. Methods: The stress-preventing effects of four anaesthetic agents (2-phenoxyethanol, 600 mg/L; metomidate, 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…However, Turek (2011) found lower lactic acid levels in an MS-222 group. Liu et al (2022) found that the sh in the anesthetized group showed a signi cant increase in serum glucose (GLU) after 12 h. Velíšek et al (2004) and Weber et al (2017) found the same trend after 24 h of anesthetization. Velíšek et al (2004 and2011) demonstrated increases in the activity of glutamic-oxalacetic transaminase (AST) after 24 hours of anesthetization.…”
Section: Introductionmentioning
confidence: 85%
“…However, Turek (2011) found lower lactic acid levels in an MS-222 group. Liu et al (2022) found that the sh in the anesthetized group showed a signi cant increase in serum glucose (GLU) after 12 h. Velíšek et al (2004) and Weber et al (2017) found the same trend after 24 h of anesthetization. Velíšek et al (2004 and2011) demonstrated increases in the activity of glutamic-oxalacetic transaminase (AST) after 24 hours of anesthetization.…”
Section: Introductionmentioning
confidence: 85%